Ahmed Zaki Validi is a scientist-turcologist (Journal of Oriental Studies, 2016)
Ahmed Zaki Validi Gaughan – is a visible political and public figure, publicist, scientist-turcologist standing at the sources of creation of the Bashkir Soviet Autonomous Republic and her first head. However, the dispute about personality of Zaki Validi does not calm down beginning in 20th of XX of century until now.In Soviet history, he was given a place nationalist, forced to flee from Soviet Russia abroad, one of the leaders Basmachi. In the early 90s begins creation of new history of Bashkortostan and interpretation of many events changes. In 1992 his name was appropriated to the republican national library. Decree of the President of Bashkortostan on September 4 in 1996 outlined measures to return in Bashkortostan scientificheritage of Validov and his colleague-emigrants and perpetuating their memory. His activity and works began to be considered exceptionally as positive. If political activity of Validi is estimated ambiguously, then as a scientist he got universal recognition at all times and everywhere, in Europe and in the East. The researchers of his biography are single in one, he was a prominent scientist-historian, turcologist and orientalist.
Keywords: Zaki Validi; history; oriental studies; Turks; emigration.